FINANCIAL AND NON-FINANCIAL INFORMATION INFLUENCING INITIAL RETURN OF IPOS ON THE INDONESIA STOCK EXCHANGE - Zuliardi, Kharisma; Witiastuti, Rini Setyo (Management Analysis Journal, 2020)
This study aims to determine the effect of financial factors (Return on Assets, Current ratio, Debt to Equity Ratio) and non-financial factors (company age and percentage of stock offer) listed in the company?s prospectus against the level of Initial Return of shares. This type of research is quantitative research, the population in this study is a company that experienced a positive initial return on the first day on the secondary market that conducted an Initial Public Offering (IPO) on the Indonesia Stock Exchange in 2013-2018 with a total of 150 issuers, while the sample amounted to 122 issuers using the sampling technique that is purposive sampling method. The analytical method used is multiple linear analysis methods using eviews9. The results of the study indicate that the independent variables namely ROA, CR, DER, AGE, and PPS affect the dependent variable initial return. Only the variable ROA and company age that affects the level of initial stock return. ROA has a significant negative effect on initial return, Company Age has a significant negative effect on initial return. While CR, DER, and Percentage of stock offerings do not affect the stock initial return. For further research, it is better to add other variables, namely market ratios and company size that have not been used in this study.